The support of early-career researchers in health professions education—an expert position statement - Doreen Herinek; Franziska Matthes; Mohamed Al-Eraky; Elizabeth Anderson; Julie Browne; Maria Cassar; Ingrid Darmann-Finck; Götz Fabry; Marion Huber; Fiona Kent; Mirjam Körner; Sylvia Langlois; et al. (Frontiers in Medicine, 2025)
IntroductionThe development of health professions education (HPE) as an academic discipline requires well-qualified educational researchers, equipped with the competence to advance the field. There is, therefore, a need to establish and support pathways in which early-career researchers (ECRs) can develop the necessary competence to pursue a career in this field.ApproachA group of 19 international experts in HPE from various professions, conducted a 2.5-day Scoping Workshop in Hannover, Germany, in November 2024. The main output of the workshop is a joint position statement on the support of ECRs in HPE, using appreciative inquiry and collaborative writing.PositionThe Scoping Workshop led to a dynamic and productive exchange of ideas and experiences resulting in a common vision and five positions: (1) identify, establish, and recognize distinct career paths, (2) develop and implement a robust funding strategy, (3) create a nurturing and diverse intellectual culture, (4) connect research to practice and address real-world problems, (5) invest in leadership, advocacy, and coaching. There was strong agreement that these areas were not well developed and required urgent attention.OutlookThere is a need to foster interprofessional and interdisciplinary collaboration and provision of sustainable support structures so that ECRs can advance HPE. Only when these areas are addressed can these educational researchers contribute to the development of effective learning which prepares the healthcare workforce to meet today’s challenges. Researchers, educators, decision-makers and stakeholders in academia, education, and health and social care contexts share a responsibility for shaping the way forward.